Migrant and mainstream perspectives on buying national: An Australian case study. (August 2021) - Fozdar, Farida
In a globalising world, people might be expected to be less nationalistic about their personal consumption decisions. Yet support for Trump-style protectionism and 'buy national' campaigns appears to be spreading. How do people talk about such purchasing decisions? Applying thematic content analysis and discourse analysis to qualitative data from 27 focus groups (n = 223) conducted across Australia, this article explores the key features of discussions about 'buying Australian', comparing migrant/ethnic minority responses with non-migrant/mainstream responses. Perhaps surprisingly, migrants adopt the taken-for-granted imperative that nationalist consumption is good for the national economy, and articulate this choice as a demonstration of loyalty and reciprocity to their adopted country. Perhaps counter to expectations, mainstream participants are far more ambivalent in the ways they express this nationalist imperative. While nationalist consumption remains the bottom line as the appropriate purchasing orientation, their position as charter group enables them to offer more critical arguments about the authenticity of the 'Australian-made' logo and the quality and price of goods. For both, however, the taken-for-granted default position is that consumer nationalism is 'the right thing to do'. Buying national is thus an instance of what Billig identified as 'banal nationalism', where the nation-state, as opposed to other collectives such as 'workers' or 'global citizens', is reproduced as the appropriate category for identification and collective responsibility.